Free Fatty Acids and Biochemical Changes in Iraqi patients with Chronic Renal Failure (Baghdad Science Journal, 2025)
Chronic renal failure (CRF) is progressive irreversible destruction of kidney tissue by disease which, if not treated by dialysis or transplant, will result in patient's death. This study was carried out on 30 patients (17 male and 13 female) with chronic renal failure. The aim of this research was studied the changes in the level of total protein ,albumin, calcium ,ionized calcium, phosphorous , iron ,ALP, LDH ,CK and FFA in patients with CRF before and after hemodialysis .The obtained results have been compared with 30 healthy subjects as control group (18male and 12 female). The results showed that there was significant increase in the level of calcium ,ionized calcium, phosphorous ,iron ,ALP,LDH,CK and FFA ,while there was a significant decrease in the level of total protein ,albumin before hemodialysis comparison to control group . Non significant changes was observed in the level of total protein ,albumin, calcium ,ionized calcium, phosphorous and significant increase in the level of iron ,ALP,LDH,CK and FFA after hemodialysis as compared to control group. This study shows significant positive correlation between FFA and each of albumin and total protein in pre and post-dialysis patients ,and a significant positive correlation with calcium and non significant with ionized calcium in pre-dialysis patients where as there were non significant correlation with calcium and a significant negative correlation with ionized calcium in post-dialysis patients. The conclusion of this study is hemodialysate composition (concentration of electrolytes, free –ionized calcium and some other plasma constituents), the increase concentration of other biochemical changes after renal dialysis because of amissibility a much of amounts of body fluids, and the change in acidosis status may be affect on the correlation between FFA and other parameters used in this study.